2009
DOI: 10.1007/s00592-009-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

The glycemic and peak incremental indices of honey, sucrose and glucose in patients with type 1 diabetes mellitus: effects on C-peptide level—a pilot study

Abstract: Our study was a case-control cross-sectional study that was conducted on 20 children and adolescents suffering from type 1 diabetes mellitus and ten healthy non-diabetic children and adolescents serving as controls. The mean age of patients was 10.95 years. Oral sugar tolerance tests using glucose, sucrose and honey and measurement of fasting and postprandial serum C-peptide levels were done for all subjects in three separate sittings. The glycemic index (GI) and the peak incremental index (PII) were then calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 30 publications
3
37
0
1
Order By: Relevance
“…[5]. It was also shown that honey has lower GIs in children (adolescence, mean age 10.95) [23,24]. In a study conducted by Atalay et al, the GI of citrus honey used in the study was found to be 44.9 and classified as low [8].…”
Section: Discussionmentioning
confidence: 99%
“…[5]. It was also shown that honey has lower GIs in children (adolescence, mean age 10.95) [23,24]. In a study conducted by Atalay et al, the GI of citrus honey used in the study was found to be 44.9 and classified as low [8].…”
Section: Discussionmentioning
confidence: 99%
“…Honey increases C-peptide levels in non-diabetic patients, yet it does not increase significantly in diabetic patients (Abdulrhman et al 2011). Honey may have a direct stimulatory effect on healthy β-cells, but its effect on defective β-cells is still unsure.…”
Section: Role Of Honey In Diabetesmentioning
confidence: 98%
“…Both GI and PII are the measures on the effects of food on the blood glucose level. In comparison to sucrose and glucose, honey has a lower GI and PII in both healthy and diabetic subjects (Abdulrhman et al 2011). However, the GI and PII differ between different types of honey based on different floral sources.…”
Section: Role Of Honey In Diabetesmentioning
confidence: 99%
See 2 more Smart Citations